2021
DOI: 10.21608/jrciet.2021.163342
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Saudi EFL Student-Teachers’ Perceptions of their Teaching Practicum

Abstract: his qualitative study aims to explore the perceptions of Saudi EFL female studentteachers of the main components of their teaching practicum namely; cooperating teachers, university supervisors, host schools and the teaching practicum itself. A total of 44 Saudi female student-teachers voluntarily participated in the study after completing their field training of their teaching practicum in government schools in Al-Madinah Al-Munawarah, KSA, the academic year 2017-2018. Data were collected by means of a 60-ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…study theoretical aspects of the curriculum, and then they are sent to schools to practice what they have learned theoretically before they step to the real world of teaching (Ibrahim, 2021;Kadir & Aziz, 2021). In this respect, the findings of Remmi and Hashim (2021) indicated that pre-service teachers' perceptions of using online formative assessment were positive.…”
mentioning
confidence: 99%
“…study theoretical aspects of the curriculum, and then they are sent to schools to practice what they have learned theoretically before they step to the real world of teaching (Ibrahim, 2021;Kadir & Aziz, 2021). In this respect, the findings of Remmi and Hashim (2021) indicated that pre-service teachers' perceptions of using online formative assessment were positive.…”
mentioning
confidence: 99%